State of the Art of Probiotic Use in Neonatal Intensive Care Units in French-Speaking European Countries - Amélie Blanchetière; Charles Dolladille; Isabelle Goyer; Olivier Join-Lambert; Laura Fazilleau (MDPI AG, 2023)
The effectiveness of probiotics in reducing the incidence of necrotizing enterocolitis has been supported by a very large number of studies. However, the utilization of probiotics in preterm infants remains a topic of debate. This study aims to assess the rate of probiotic use in European neonatal intensive care units (NICUs), compare administration protocols, and identify barriers and concerns associated with probiotic use. An online questionnaire was distributed via email to European NICUs between October 2020 and June 2021. Different questions related to the frequency of probiotic use were proposed. Data on probiotic administration protocols and reasons for non-utilization were collected. The majority of responses were from France and Switzerland, with response rates of 85% and 89%, respectively. A total of 21% of French NICUs and 100% of Swiss NICUs reported routine probiotic use. There was significant heterogeneity in probiotic administration protocols, including variations in probiotic strains, administration, and treatment duration. The main obstacles to routine probiotic use were the absence of recommendations, lack of consensus on strain selection, insufficient scientific evidence, and concerns regarding potential adverse effects. The rate of routine probiotic administration remains low in European NICUs, with heterogeneity among protocols. Further trials are necessary to elucidate optimal treatment modalities and ensure safety of administration.